The effect of sensory marketing elements on repurchase intention of Pakistan Airlines - Ali, Jawad (2021)
This research focused on factors of sensory marketing that drives airline image and repurchase intention towards passengers of Pakistan based airline companies. This research differentiates itself from other studies as it examined the mediating role of airline image in the airline sector of a developing country. Present study also tested the moderating role of perceived price fairness and word of mouth towards repurchase intention. A cross-sectional design was followed in this research, data was collected from three airports of Pakistan. Research questionnaires were distributed among 576 passengers of Airblue and PIA using judgmental sampling approach. PLS-SEM analysis approach was utilized in this study. The results of the present study found that visual stimuli, auditory stimuli, touch stimuli and gustatory stimuli have positive relationship with airline image. The results also supported mediating role of airline image between visual stimuli, auditory stimuli, gustatory stimuli, touch stimuli and repurchase intention. Moreover, perceived price fairness moderates between airline image and repurchase intention. The findings of the present study provide important insights to airline industry researcher, marketers and policy makers. The marketers of airline industry can get guidance to design effective marketing strategy by focusing on sensory marketing factors. On the other hand, policy makers can enhance growth of Pakistan based airline firms by following the recommendations of the study. The research also highlights the limitations and implications of the study as well as suggestions for future research are mentioned as well.